A Swarm of WASP Planets: Nine Giant Planets Identified by the WASP Survey - N. Schanche; G. Hébrard; K. G. Stassun; B. Hord; K. Barkaoui; A. Bieryla; D. Ciardi; K. A. Collins; A. Collier Cameron; J. Hartman; N. Heidari; C. Hellier; et al. (The Astronomical Journal)
The Wide Angle Search for Planets (WASP) survey provided some of the first transiting hot Jupiter candidates. With the addition of the Transiting Exoplanet Survey Satellite (TESS), many WASP planet candidates have now been revisited and given updated transit parameters. Here, we present nine transiting planets orbiting FGK stars that were identified as candidates by the WASP survey and found to have planetary masses via radial velocity measurements. Subsequent space-based photometry taken by TESS as well as ground-based photometric and spectroscopic measurements have been used to jointly analyze the planetary properties of WASP-102 b, WASP-116 b, WASP-149 b WASP-154 b, WASP-155 b, WASP-188 b, WASP-194 b/HAT-P-71 b, WASP-195 b, and WASP-197 b. These planets have radii between 0.9 R _Jup and 1.4 R _Jup , masses between 0.1 M _Jup and 1.5 M _Jup , and periods between 1.3 and 6.6 days.